Potential of Essential Oils - El-Shemy, Hany A. (IntechOpen, 2018)
Essential oils have recently received much attention globally due to the increased use of essential oils as well as the positive impacts from economic backgrounds. New compounds of essential oils have been discovered from medicinal plants and used in anti-disease treatment as well as in most houses as a source of natural flavor. This book covers some interesting research topics for essential oils, including identification of active ingredients from wild and medicinal plants. This book will add significant value for researchers, academics, and students in the field of medicine.